Phenolic profile and content of sorghum grains under different irrigation managements - Wu, G.; Bennett, Sarita; Bornman, J.; Clarke, M.; Fang, Z.; Johnson, Stuart (Elsevier, 2017)
Sorghum grain is widely consumed in Sub-Saharan Africa and Asia, as a staple food due to its adaptation to harsh environments. The impact of irrigation regime: full irrigation (100%); deficit irrigation (50%); and severe deficit irrigation (25%) on phenolic profile and content of six sorghum grain genotypes was investigated by high performance liquid chromatography coupled with diode array detection and electrospray ionization mass spectrometry (HPLC-DAD-ESI-MS). A total of 25 individual polyphenols were unequivocally or tentatively identified. Compared to the colored-grain genotypes, the white grained sorghum var. Liberty had a simpler polyphenol profile. The concentrations of the sorghum-specific 3-deoxyanthocyanidins luteolinidin and apigeninidin, were higher under deficit irrigation compared to the other two regimes in all genotypes. These findings will be valuable for the selection of sorghum genotypes for grain production as human food under water deficit conditions, since polyphenol levels can affect the grain's nutritional value and health properties.